Design of Mechanical Systems for Princes Hotel Building - Abo Khurj, Imad; Shalabi, Obaida (جامعة بوليتكنك فلسطين - ميكانيك, 2021)
This project aims to design the mechanical systems for Princes Hotel which is located in Bethlehem. This building consists of nine floors with an area of 2515.4 m2 . In this project, the thermal loads of this building calculated and the appropriate air conditioning system will be selected. The project also includes calculations, material selection, bill of quantities preparation for air conditioning system, ventilation system, water system, drainage system and firefighting system. These services are definitely designed to check human comfort. الملخص: يهدف هذا المشروع إلى تصميم االنظمة الميكانيكية لفندق االميرة الذي يقع في بيت لحم. يتكون هذا المبنى من عشرة طوابق م2515.4 بمساحة 2 . في هذا المشروع ، حيث تم حساب األحمال الحرارية لهذا المبنى و اختيار نظام تكييف الهواء المناسب. ويشمل المشروع أي ًضا الحسابات واختيار المواد وإعداد الفواتير لنظام تكييف الهواء ونظام التهوية ونظام المياه ونظام الصرف ونظام مكافحة الحرائق. تم تصميم هذه الخدمات بالتأكيد للتحقق من راحة اإلنسان.
no of pages 155 , ميكانيك 1/2021
Keywords: Mechanical Systems